2 μm solid-state laser mode-locked by single-layer graphene - Lagatsky,AA; Sun,Z; Kulmala,TS; Sundaram,RS; Milana,S; Torrisi,F; Antipov,OL; Lee,Y; Ahn,JH; Brown,CTA; Sibbett,W; Ferrari,AC (Applied Physics Letters, 2013)
We report a 2 μm ultrafast solid-state Tm: Lu2O3 laser, mode-locked by single-layer graphene, generating transform-limited ∼ 410 fs pulses, with a spectral width ∼ 11.1 nm at 2067 nm. The maximum average output power is 270 mW, at a pulse repetition frequency of 110 MHz. This is a convenient high-power transform-limited ultrafast laser at 2 μm for various applications, such as laser surgery and material processing. © 2013 American Institute of Physics.